Teacher’s Leadership n Developing Character of Early Childhood: Case Study at Harapan Bunda Kindergarten, Jambi City - Rusmini, Rusmini; Samsu, Samsu (AT-TA'LIM, 2023)
The purpose of this article is to describe the role of teacher leadership as a model for early childhood character development, as well as the difficulties in developing children's character. The study uses a qualitative approach in describing situations from social reality. Data was obtained through observation, interviews, and documentation, and analyzed using data reduction, data display, verification, and conclusion. This study concludes that the teacher's leadership role can shape the childhood independent character. Firstly, the role of teacher leadership in learning as a model of childhood independence for habituation. Secondly, there are childhood independent characters in daily activities. Thirdly, there are difficulties faced by teachers in realizing independent characters for children. This study recommends that teachers need to be given leadership reinforcement in early childhood character development so that they can develop optimally.